User Response - Based Sustainable Solutions to Traffic Congestion Problem using Public Transport: The Case of Uttara, Dhaka - ATM Abir; MD Mostafizur Rahman; Farjana Islam; Raisa Bashar; Sirajul Islam (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2018)
For a country of millions, traffic congestion significantly reduces the economic productivity. This statement holds true for most urban areas of the world, especially Dhaka, the mega-city of Bangladesh. An area of Dhaka which has a lot of potential in terms of both as a residential and commercial region, is undoubtedly the suburb of Uttara. Along with being adjacent to the airport on one side and having a link to industrial areas like Gazipur and Savar on the other, it also has residential amenities in its numerous blocks, making it a colony for traffic congestion. Unfortunately, no sustainable solution has come about to successfully reduce this problem. Hence, this paper tries to understand where the problems lie from the perspectives of the most important stakeholders - the residents and commuters of the area. It supports the use of their simple thinking to reach solutions through suasive instruments, like training and awareness-building campaigns, instead of spending millions on building lengths of roads and investing in technology. A survey of 150 bus passengers and 150 private car owners, coupled with literature review were conducted to accumulate, identify and address the traffic congestion reasons and associated issues. These problems were later used to propose recommendations. Responses revealed that the satisfaction levels of the commuters fell mostly under the 'dissatisfied' category (78%), based on parameters like fitness of the bus and driver, behavior of drivers and conductors, etc. Unsurprisingly, most respondents showed interest to pay an extra bit of fare for better bus service and believed that these would greatly help to mitigate the issue of running this sector with 'unskilled' and 'unprofessional' drivers/conductors (92%). Additionally, the large presence of private cars seemed to cause higher amounts of traffic congestion, but 56% of these users believed that the public buses had poor service and hence, their decision to avoid it as a regular commuting option. Hence, it was clear from the responses and their analysis that only a reliable, comfortable, and safe bus service system (including good drivers, conductors and buses themselves) is what will encourage more people to travel in public buses, leaving behind their private cars. This would in turn, greatly reduce the traffic congestion problem as people will be able/want to follow the traffic regulations better.